Traffic density on the road network axes in the city of Misurata in 2024 and forecasts for 2034 (A study in transport geography) - جمال إبراهيم محمد رمضان (Journal of Libyan Academy Bani Walid, 2025)
This study aims to identify the problems and shortcomings affecting the road network, specifically the difficulty of movement for people and goods on the road axes in the study area during peak hours. The research problem stemmed from observing traffic congestion at certain points along the network's main arteries. Consequently, the researcher conducted a field study at 15 points using a direct count method (traffic survey) to measure the flow of traffic on these axes during peak hours (vehicles/hour). The study required the description, measurement, and analysis of traffic flow. The researcher used several approaches, including the historical method to trace the evolution of the phenomenon over time, and the descriptive method to describe and analyze its components. Quantitative techniques were used to analyze the data, which was then represented in charts, graphs, and maps. The study's findings indicate that some road axes suffer from high traffic flow density, exceeding the road's carrying capacity. These axes require immediate treatment and widening. In contrast, the current traffic density on other axes does not conflict with the road's capacity, which is attributed to the road's width being commensurate with the volume of traffic. The study also provided future projections for the roads for 2034, with the researcher predicting that most axes will suffer from future traffic bottlenecks. It is expected that traffic density will increase beyond the carrying capacity, necessitating treatment in the coming years as part of a road development plan. The study recommended redesigning intersections, junctions, and traffic signals, and prioritizing roundabouts, overpasses, and pedestrian bridges to reduce movement delays. It also recommended stricter enforcement of penal legislation against those who use road sidewalks for commercial activities and urban planning legislation that mandates the allocation of parking spaces when issuing building permits. The study also recommended shifting towards the use of public transport, which in turn would alleviate the use of private vehicles